2021
DOI: 10.1002/ieam.4448
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal patterns and driving factors of carbon dynamics in forest ecosystems: A case study from Turkey

Abstract: Evaluating the spatiotemporal patterns of carbon dynamics is critical for both understanding the role of forest ecosystems in the carbon cycle and developing effective forest policies to mitigate the impacts of climate change. This study analyzes the effects of spatiotemporal changes on carbon dynamics based on landscape structure for the Hisar Planning Unit, Turkey, using forest inventory data between 1973 and 2015. The total carbon stock increased from 1434 .49 Gg in 1973 to 1919 Gg in 2015, an increase of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 70 publications
0
1
0
Order By: Relevance
“…Topographic factors, including elevation, slope, and aspect, had been widely considered to be the main factors affecting the spatial pattern of forest biomass [12,13]. Socio-economic drivers, including gross domestic product (GDP) and population (POP), also play an irreplaceable role [14]. Alves et al [15] studied the aboveground biomass and forest structure on the elevation gradient in the humid zone of the tropical Atlantic in Brazil, and it was found that the distribution of aboveground biomass was affected by the local scale topographic changes related to elevation.…”
Section: Introductionmentioning
confidence: 99%
“…Topographic factors, including elevation, slope, and aspect, had been widely considered to be the main factors affecting the spatial pattern of forest biomass [12,13]. Socio-economic drivers, including gross domestic product (GDP) and population (POP), also play an irreplaceable role [14]. Alves et al [15] studied the aboveground biomass and forest structure on the elevation gradient in the humid zone of the tropical Atlantic in Brazil, and it was found that the distribution of aboveground biomass was affected by the local scale topographic changes related to elevation.…”
Section: Introductionmentioning
confidence: 99%